What them old bones can teach us - Cassella, John (The University of Hull)
This document contains activities for tutors to offer to students. These activities develop from the basic understanding of the ethical handling of human bone remains and develop through to the understanding of skeletal anatomy. As the activities develop, the role of foresnsic pathology of skeletal remains is examined. There are also basic activities to introduce the concepts of archaeology and context of the materials recovered in an archaeologial setting.